Named Entity Recognition for Kashmiri Language using Noun Identification and NER Identification Algorithm - Bashir Malik, Amir; Bansal, Khushboo (International Journal of Computer Sciences and Engineering, 2025)
In this study, we present a brief overview of Named Entity Recognition (NER) system, various approaches followed for NER systems and finally NER systems for Kashmiri language. Kashmiri language raises several challenges to Natural Language Processing (NLP) largely due to its rich morphology. Named entity recognition (NER) (also known as entity identification and entity extraction) is one of the important subtask of information extraction that seeks to locate and classify atomic text into predefined categories such as the names of persons, organizations, locations, monetary values, percentages, expressions of times, etc. This paper describes the problems of NER in the context of Kashmiri Language and provides relevant solutions by using noun identification algorithm and named entity recognition identification algorithm Building a named entity recognition system for Kashmiri languages that can understand Kashmiri language has been one of the long-standing goals of (NER) system.